Prólogo - Fernandez, Sergio Gustavo (REVISTA JURÍDICA UNIVERSIDAD NACIONAL DEL OESTE, 2026)
I am deeply grateful for the invitation to write the foreword for a new edition of the Revista Jurídica (Legal Journal), a publication of the Institute of Education, Justice, and Labor at the National University of the West (Universidad Nacional del Oeste). I present here the sixth issue of this publication, which, semester after semester, has grown in relevance within the legal discourse of our country and the region, and which has been declared of legislative interest by the Honorable Senate and the Honorable Chamber of Deputies of the Province of Buenos Aires, as well as of municipal interest by the Honorable Deliberative Council of Merlo.